Formulasi dan Karakterisasi Nanoemulsi Ekstrak Etanol Buah Wualae (Etlingera Elatior (Jack) R.M. Smith): Formulation and Characterization of Nanoemulsion Ethanol Extract of Wualae (Etlingera Elatior (Jack) R.M. Smith) - Wa Ode Sitti Zubaydah; Astrid Indalifiany; Yamin; Suryani; Dian Munasari; Muhammad Handoyo Sahumena; Sitti Raodah Nurul Jannah (Lansau: Jurnal Ilmu Kefarmasian, 2023)
Wualae (Etlingera elatior (Jack) R.M. Smith) has a high flavonoid content, so it has the potential as an antioxidant and can be used in drug delivery systems, namely nanoemulsions. Nanoemulsions can improve absorption, help dissolve lipophilic drugs and increase bioavailability. This study aims to determine the formulation and characterization of wualae nanoemulsion. The research method used is a low-energy emulsification method. The nanoemulsion is formulated into four formulas with a concentration ratio of tween 80 and PEG 400, namely 50%: 30% (F1), 50%: 10% (F2), 10%: 30% (F3), and 10%: 10% (F4). The characterizations included organoleptic tests, nanoemulsion type tests, viscosity tests, transmittance tests, particle size tests, polydispersity index tests, potential zeta and physical tests, and centrifugation and cycling tests. The results obtained sequentially are F1 has a characteristic odour of clear yellow, type of oil-in-water nanoemulsion, 150 cPa.s, 99%, 14.56 ± 0.666 nm, 0.061 ± 0.017, 1.453 ± 1.23 mV and is stable in the test. F2 has a characteristic odour of clear yellow colour, oil-in-water nanoemulsion type, 900 cPa.s, 97.2%, 13.8 ± 0.781 nm, 0.126 ± 0.066, -5.503 ± 0.57 mV and is stable in difficult tests. F3 has a dirty white type of nanoemulsion oil in 9.5 cPa and is unstable in typical tests. F4 has a characteristic odour of cloudy white colour, oil-in-water nanoemulsion type, 6 cPa.s and is inconsistent in stability testing. Based on the data above, the best wualae fruit extract nanoemulsion formulation is formula 1.